2008
DOI: 10.1167/8.15.7
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual short-term influences and aftereffects in motion: Examination across three sets of directional pairings

Abstract: The study of cross-modal influences in perception, particularly between the auditory and visual modalities, has been intensified recently. This paper reports on a comprehensive study of auditory-visual cross-modal influences in motion, including motion aftereffects (MAE). We examined both auditory influences on visual perception and vice versa. Visual motion interactions were examined using three directional pairings or configurations: along the horizontal, vertical, and depth axes. In Experiment 1 we assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…Together, the results of Experiment 1 are in line with studies showing visual modulation of audio motion in depth perception (Harrison, 2012;Jain et al, 2008). Similarly, enhanced behavioural responses for looming visual stimuli have previously been reported in unimodal (Ball & Tronick, 1971;Schiff et al, 1962) and multimodal (Cappé et al, 2009;Harrison, 2012) paradigms, and have been interpreted to be a result of the adaptive salience of approaching objects.…”
Section: Discussionsupporting
confidence: 89%
“…Together, the results of Experiment 1 are in line with studies showing visual modulation of audio motion in depth perception (Harrison, 2012;Jain et al, 2008). Similarly, enhanced behavioural responses for looming visual stimuli have previously been reported in unimodal (Ball & Tronick, 1971;Schiff et al, 1962) and multimodal (Cappé et al, 2009;Harrison, 2012) paradigms, and have been interpreted to be a result of the adaptive salience of approaching objects.…”
Section: Discussionsupporting
confidence: 89%
“…Using RDK stimuli marks an important deviation from the previous literature on cross-modal MAEs (e.g., Jain et al, 2008), as RDK stimuli lack any trackable visual features and have a much richer spatiotemporal frequency content. Each RDK stimulus consisted of 100 moving dots.…”
Section: Methodsmentioning
confidence: 88%
“…It is thus possible that the pitch-verticality correspondence is a stronger metaphoric mapping, and thus can elicit a visual MAE from purely auditory adaptation. This is one of the hypotheses tested by Jain, Sally, and Papathomas (2008). They found that after adaptation to continuously rising or falling auditory motion, participants were more likely to judge ambiguous sinusoidal gratings as moving in the opposite direction.…”
mentioning
confidence: 92%
“…Neurophysiological and imaging studies have enabled scientist to clarify the role of multisensory areas in the brain, like the SC [2]. We have developed a computational model that explains the interactions between auditory and visual motion mechanisms as observed by Jain et al [1]. These interactions are mediated by the feedback connections from the integrative multimodal areas (SC) to the unimodal areas in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…
Jain et al [1] showed that a strong motion signal in one modality (visual/auditory) influences the perception of a simultaneously present weak motion signal in the other modality (auditory/visual) for motion along the three cardinal axes. Furthermore, they also observed auditory crossmodal motion aftereffects (MAE) for all directions and visual crossmodal MAE for vertical direction of motion.
…”
mentioning
confidence: 99%